1998
DOI: 10.1164/ajrccm.157.4.9703099
|View full text |Cite
|
Sign up to set email alerts
|

Reduced E-Cadherin Expression Is Associated with Increased Lymph Node Metastasis and Unfavorable Prognosis in Non-small Cell Lung Cancer

Abstract: E-cadherin is a calcium-dependent, epithelial cell adhesion molecule whose reduced expression has been associated with tumor dedifferentiation and increased lymph node metastasis in clinical studies involving several carcinomas. In this study, 111 patients who had previously undergone complete resection and systematic mediastinal lymph node dissection for non-small cell lung cancer (NSCLC) were studied retrospectively. In the primary tumor, as well as in the lymph node metastases, E-cadherin expression was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
67
2
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 20 publications
11
67
2
3
Order By: Relevance
“…In addition, VEGF-C expression, another member of the VEGF family and reported to induce lymphangiogenesis (Skobe et al, 2001), was also associated with the prognosis of stage I patients, as reported previously (Kajita et al, 2001;Arinaga et al, 2003). Furthermore, previous clinical studies have shown that reduced expressions of several metastatic suppressor genes, including E-cadherin (Sulzer et al, 1998;Liu et al, 2001), MRP-1/CD9, and KAI1/CD82 , are also associated with nodal metastases and a poor prognosis of patients with stage I NSCLCs. Although there were a few wide CIs for the hazard ratios in Table 4, these results might be partly because of factors like differing follow-up.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In addition, VEGF-C expression, another member of the VEGF family and reported to induce lymphangiogenesis (Skobe et al, 2001), was also associated with the prognosis of stage I patients, as reported previously (Kajita et al, 2001;Arinaga et al, 2003). Furthermore, previous clinical studies have shown that reduced expressions of several metastatic suppressor genes, including E-cadherin (Sulzer et al, 1998;Liu et al, 2001), MRP-1/CD9, and KAI1/CD82 , are also associated with nodal metastases and a poor prognosis of patients with stage I NSCLCs. Although there were a few wide CIs for the hazard ratios in Table 4, these results might be partly because of factors like differing follow-up.…”
Section: Discussionsupporting
confidence: 74%
“…For example, the activation of oncogenes or the inactivation of tumour suppressor genes, such as K-ras mutation and p53 mutation, could initially cause malignant progression . In addition, reduced expressions of metastatic suppressor genes, such as E-cadherin (Sulzer et al, 1998;Liu et al, 2001), MRP-1/CD9, and KAI1/CD82 , could induce tumour cells with high metastatic potential. In addition, tumour angiogenesis, affected by various angiogenetic factors such as the VEGF family (Dvorak et al, 1995), is associated with not only tumour growth but also tumour metastasis (Folkman, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epithelial cell adhesion molecule is an epithelial differentiation marker, which is frequently expressed on normal epithelial cells (Winter et al, 2003). Loss of Ep-CAM expression is therefore a likely consequence of tumour cell de-differentiation, as for instance is seen for the epithelial differentiation antigen E-cadherin (Sulzer et al, 1998). On the other hand, overexpression or maintenance of Ep-CAM expression on tumour cells relative to normal epithelia may then be an indication that its presence confers a benefit to tumour cells.…”
Section: Discussionmentioning
confidence: 99%